A risk prediction model for the development of subsequent primary melanoma in a population‐based cohort. (1st May 2020) - Cust, A.E.; Badcock, C.; Smith, J.; Thomas, N.E.; Haydu, L.E.; Armstrong, B.K.; Law, M.H.; Thompson, J.F.; Kanetsky, P.A.; Begg, C.B.; Shi, Y.; Kricker, A.; et al.
Summary: Background: Guidelines for follow‐up of patients with melanoma are based on limited evidence. Objectives: To guide skin surveillance, we developed a risk prediction model for subsequent primary melanomas, using demographic, phenotypical, histopathological, sun exposure and genomic risk factors. Methods: Using Cox regression frailty models, we analysed data for 2613 primary melanomas from 1266 patients recruited to the population‐based Genes, Environment and Melanoma study in New South Wales, Australia, with a median of 14 years' follow‐up via the cancer registry. Discrimination and calibration were assessed. Results: The median time to diagnosis of a subsequent primary melanoma decreased with each new primary melanoma. The final model included 12 risk factors. Harrell's C ‐statistic was 0·73 [95% confidence interval (CI) 0·68–0·77], 0·65 (95% CI 0·62–0·68) and 0·65 (95% CI 0·61–0·69) for predicting second, third and fourth primary melanomas, respectively. The risk of a subsequent primary melanoma was 4·75 times higher (95% CI 3·87–5·82) for the highest vs. the lowest quintile of the risk score. The mean absolute risk of a subsequent primary melanoma within 5 years was 8·0 ± SD 4.1% after the first primary melanoma, and 46·8 ± 15·0% after the second, but varied substantially by risk score. Conclusions: The risk of developing a subsequent primary melanoma varies considerably between individuals and is particularly high for those with two or more primary melanomas. The risk prediction model and its associated nomograms enable estimation of the absolute risk of subsequent primary melanoma, on the basis of on an individual's risk factors, and can be used to tailor surveillance intensity, communicate risk and provide patient education. What's already known about this topic? Current guidelines for the frequency and length of follow‐up to detect new primary melanomas in patients with one or more previous primary melanomas are based on limited evidence. People with one or more primary melanomas have, on average, a higher risk of developing another primary invasive melanoma, compared with the general population, but an accurate way of estimating individual risk is needed. What does this study add? We provide a comprehensive risk prediction model for subsequent primary melanomas, using data from 1266 participants with melanoma (2613 primary melanomas), over a median 14 years' follow‐up. The model includes 12 risk factors comprising demographic, phenotypical, histopathological and genomic factors, and sun exposure. It enables estimation of the absolute risk of subsequent primary melanomas, and can be used to tailor surveillance intensity, communicate individual risk and provide patient education.